2022
DOI: 10.3389/fpubh.2022.850872
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Urbanization on Health Care Expenditure: Evidence From China

Abstract: This paper investigates the impact and non-linear effects of urbanization on health care expenditure in China. The results indicate that urbanization in both Eastern and Central regions can significantly increase health care expenditure. But the impact of urbanization is not significant, which is related to the backward economic development level and low urbanization rate in the Western region. Taking population aging into consideration, the results of the panel threshold regression model imply that the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 72 publications
3
10
0
1
Order By: Relevance
“…Economic activity increases pollution and health expenses (16). Globalization increases the urban population, which positively impacts health expenditures (28). The impact of renewable energy on health expenditures is in-line with Sasmaz et al (21).…”
Section: Long-run Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Economic activity increases pollution and health expenses (16). Globalization increases the urban population, which positively impacts health expenditures (28). The impact of renewable energy on health expenditures is in-line with Sasmaz et al (21).…”
Section: Long-run Resultssupporting
confidence: 84%
“…Nevertheless, in the existing literature, a few studies have examined the factors in the health sector. The following sets of studies are in-line with prevalent literature (16, 21, 25,28,34,37). The government's involvement in the health sector spending and investment, and also managing its funds for improvement in sustainable development, must be focused on for better public health.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 52%
See 1 more Smart Citation
“…As shown in Table 8, regarding the validity of the tool variables, the model selected the Hansen test as the overidentification constraint test. The model utilizes the observed values of the threshold variables to estimate the appropriate threshold, thus avoiding the insufficiency of subjective judgment partitions and yielding more accurate results (Shao et al, 2022). The model also verifies whether the residual term is autocorrelated with the firstand second-order sequences by judging the p-value of AR (He al., 2022).…”
Section: Regression Analysismentioning
confidence: 99%
“…In contrast, some studies have shown that the expansion of cities causes environmental pollution problems, increases the concentration of PM2.5, causes air pollution, and threatens the health of residents (Lu et al 2021 ; Liu et al 2022 ; Dong et al 2021 ). Besides, urbanization has changed the personal life and work style and increased the health burden of residents (Gong et al 2012 ; Li et al 2016 ) and health care expenditure (Shao et al 2022 ), thereby increasing the health risks of residents.…”
Section: Literature Reviewmentioning
confidence: 99%